Meningkatkan Partisipasi Pondok Pesantren dalam Penyampaian Laporan E-SPT Wajib Pajak Orang Pribadi dengan Program 3C di Tengah Pandemi Covid-19 - Bramasto, Ari; Harissa, Puti; Anggrahini, Muliastuti (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2020)
The Click, Call, and Counter (3C) program is considered capable to accelerate the realization of services through electronic channels. Moreover, electronic channels, such as telephone, chat, email, and others opened by the Direktorat Jenderal Pajak are greatly utilized by taxpayers ahead of the deadline for reporting the annual SPT which ends on April 30, 2020. Later, electronic services will be the first to be used independently (Click). If there are any difficulties, you can immediately ask for help through the contact center (Call), and if you still need services directly, taxpayers can come directly to the tax office (Counter). The survey results using a questionnaire, from 25 participants who took part in the socialization. 23 (92%) participants could use e-SPT reporting independently, while the remaining 2 (8%) participants had not been able to use online facilities, constrained by limited knowledge related to internet use.